Estimación del potencial de captura de carbono, del bosque natural secundario en el centro de producción e investigación Pabloyacu - Noriega Morán, Jeceli Danuci (2011)
This research project has information that is handled for basic reference and other purposes, on the estimation of carbon sequestration in the natural forest secondary. It is very important the result; since it can 'be work future projects to the decrease of atmospheric concentrations through the capture of atmospheric carbon (absorption by natural stores). Our region has the highest rate of deforestation at the national leve! by releasing enormous amounts of carbon dioxide which are leading to changes in climate and environmental quality. lt is therefore very important that the research was conducted in the Pabloyacu Research and Production Center , there are initiatives both of teachers as professionals and graduates students in conductii1g research in that place. The entry into force of the Kyoto Protocol and the clean development mechanism opens up the prospect for the forestry producers to capture financia! benefits from the sequestration services that offer their activities. This is possible thanks to the fact that forestry projects that apply successfully to the MLD may generate emissions reduction certificates that can be marketed. (Alegre et a/1998). The carbon sequestration potential in the Secondary Natural Forest belongs to the "Pabloyacu" Research and Production Center at the Ecology Faculty is approximately 4,818 ton. /Ha of Carbon result that was worked by the non-destructive method in one hectare of study. This work seelcs to worry various interests including foray into the business of carbon credits in the long term.